1997
DOI: 10.1016/s0092-8674(00)80482-1
|View full text |Cite
|
Sign up to set email alerts
|

The Rho GTPase and a Putative RhoGEF Mediate a Signaling Pathway for the Cell Shape Changes in Drosophila Gastrulation

Abstract: The Rho GTPases mediate actin rearrangements that are likely to be required for the numerous cell shape changes in a developing embryo. In a genetic screen for Rho signaling pathway components in Drosophila, we identified a gene, DRhoGEF2, that encodes a predicted Rho-specific guanine nucleotide exchange factor. Embryos lacking DRhoGEF2 fail to gastrulate due to a defect in cell shape changes required for tissue invagination, and expression of a dominant-negative Rho GTPase in early embryos results in similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
347
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(358 citation statements)
references
References 57 publications
(26 reference statements)
10
347
0
1
Order By: Relevance
“…Indeed, both fog and cta mutants exhibit a phenotype similar to the twist mutant and lack the coordinated apical constriction phase (Sweeton et al, 1991;Costa et al, 1994;Morize et al, 1998). A similar, but more severe, phenotype is observed for RhoGef2 mutants, and for Rho1 dominant negative expressing embryos (Barrett et al, 1997;Hacker and Perrimon, 1998).…”
Section: The Cellular Mechanisms That Control Cell Shape Changes Downsupporting
confidence: 65%
See 2 more Smart Citations
“…Indeed, both fog and cta mutants exhibit a phenotype similar to the twist mutant and lack the coordinated apical constriction phase (Sweeton et al, 1991;Costa et al, 1994;Morize et al, 1998). A similar, but more severe, phenotype is observed for RhoGef2 mutants, and for Rho1 dominant negative expressing embryos (Barrett et al, 1997;Hacker and Perrimon, 1998).…”
Section: The Cellular Mechanisms That Control Cell Shape Changes Downsupporting
confidence: 65%
“…Once secreted, Fog is thought to activate a G a protein, Concertina (Cta), via a yet-unknown receptor . The last steps of this pathway involves the activation of Rho via RhoGef2 and the subsequent remodelling of the actin network (Barrett et al, 1997;Hacker and Perrimon, 1998). Indeed, both fog and cta mutants exhibit a phenotype similar to the twist mutant and lack the coordinated apical constriction phase (Sweeton et al, 1991;Costa et al, 1994;Morize et al, 1998).…”
Section: The Cellular Mechanisms That Control Cell Shape Changes Downmentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila, it has been reported that DRhoGEF2, which is a putative Rho-speci®c guanine nucleotide exchange factor and Drosophila Rho regulate cell shape changes during gastrulation, and that the phenotype of embryos lacking DRhoGEF2 or expressing dominant- negative Rho is similar to that of cta, a Drosophila homologue of Ga 12 and Ga 13 , mutant (Barrett et al, 1997;HaÈ cker and Perrimon, 1998). In addition, it has been shown that Rho is required for the establishment of tissue polarity in the developing eye and wing hair in Drosophila, and that JNK-like kinases are involved in the Rho-mediated polarity signaling (Strutt et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Coordination of apical constriction requires a secreted ligand, folded gastrulation (Fog; Costa et al 1994) acting upstream of concertina (Cta), which encodes a Ga protein (Parks & Wieschaus 1991;Morize et al 1998), through G-protein-coupled receptor that has not been identified. Downstream of concertina, the rho activator, DRhoGEF2, and Rho1 are essential for the accumulation of myosin II at the cell apices (Barrett et al 1997;Hacker & Perrimon 1998;Nikolaidou & Barrett 2004;Rogers et al 2004;Dawes-Hoang et al 2005). But DRhoGEF2 also has a Fog/Cta-independent role in actin localization at the apices of the cells (Fox & Peifer 2007).…”
Section: What Is the Molecular Mechanism Of Progressive Expression Ofmentioning
confidence: 99%